Keys to the kingdom : impressioning, privilege escalation, bumping, and other key-based attacks against physical locks - Ollam, Deviant (Syngress, 2012)
Lockpicking has become a popular topic with many in the security community. While many have chosen to learn the fine art of opening locks without keys, few people explore the fascinating methods of attack that are possible WITH keys. Keys to the Kingdom addresses the topics of impressioning, master key escalation, skeleton keys, and bumping attacks that go well beyond any treatment of these topics in the author's previous book, Practical Lock Picking. This material is all new and focuses on locks currently in use as well as ones that have recently emerged on the market. Hackers and pen testers or persons tasked with defending their infrastructure and property from invasion will find these techniques uniquely valuable. As with Deviant Ollam's previous book, Practical Lock Picking, the DVD that accompanies Keys to the Kingdom includes full-color versions of all diagrams and photographs, along with instructional videos that provide readers with a full-on training seminar from the author. Excellent companion to Deviant Ollam's Practical Lock Picking. Understand the typical failings of common security hardware in order to avoid these weaknesses. Learn advanced methods of physical attack in order to be more successful with penetration testing. Detailed full-color photos in the book make learning easy, and companion website is filled with invalualble training videos from Dev!